Open for Business (Raton Range Raton Range, 1991)
Article is about the opening of the New Municipal building in Cimarron, New Mexico.
Newspaper article + Photograph of the Cimarron Municipal Building
Mater List Item # 8
File location is in the New Mexico File Cabinets
Keywords: Village of Cimarron Administrators; Municipal Buildings; Building Openings; City Offices; Libraries; Police Departments; Health Clinics; Cimarron, New Mexico